André Reicherts attempts on the materiality of 'thinking' in flow and motion (KULT_online, 2014)
In his study „Diagrammatik des Denkens. Descartes und Deleuze” André Reichert develops an understanding of ‚thinking’ as flow and motion just temporarily consolidating in the ‚Gestalt’ of a specific system of thought. Instead of signifier and signified ‚Denkfigur’ (figure of thought) and ‚Denkdiagramm’ (diagram of thought) configure its possibilities and impossibilities. Using the example of René Descartes and Gilles Deleuze Reichert shows how this perspective can unveil new aspects of seemingly well-known philosophies.